Optimization of Seed Proportions of Mung Bean (Vigna radiata L.) and Planting Patterns for Sorghum (Sorghum bicolor L.) -Mung Bean Intercropping in Lasta District, North Wollo Zone, Ethiopia - Assefa, Abebe; Abate, Mesfin; Haile, Mekides; Hunegnaw, Yirsaw (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Abebe Assefa 1, Mesfin Abate2, Mekides Haile 3 and Yirsaw Hunegnaw21Amhara Regional Agricultural Research Institute (ARARI), Sekota Dry Land Agricultural Research Centre (SDARC), Sekota, Ethiopia2Debre Markos University, College of Agriculture and Natural Resources, Debre Markous, Ethiopia3Tach Armacho District Agricultural Offices, Central Gondar, Gondar, EthiopiaCorresponding author e-mail address: - assefaabebe986@yahoo.comABSTRACTIntercropping sorghum (Sorghum bicolor L.) and Mung bean (Vigna radiata) in lasta is a common practices. However, the optimal seed proportions and the appropriate planting pattern for a sorghum-mung bean intercropping system in the district have not been fully investigated. Therefore, this experiment was conducted in 2022 at Lasta district, North Wollo Zone, Ethiopia, to determine the optimal mung bean seed proportion for intercropping with sorghum and to identify the best sorghum-mung bean planting pattern and combination. Three seed proportions of mung bean (100%, 67% and 50% ) with three sorghum-mung bean planting pattern (1S:1M, 2S:1M, and 3S:1M) including sole sorghum and mung bean as a control with three replication were tested using RCBD factorial arrangements. Data on the agronomic attributes of the component crops in a mixture such as days to heading and maturity, panicle length, plant height, biomass grain yield for main crop and days to 50% flowering, 90% physiological maturity, the number of pods per plant, the number of branches per plant, the number of seeds per pod, biomass and seed yield were collected in the field and analysis using SAS software. The analysis of variance results indicated that most of the study traits were significantly affected by the seed proportions of mung bean and sorghum-mung bean planting patterns. The highest grain yield of sorghum (3030.93 kg ha-1 and 3020.43kg ha-1) was obtained within 2S:1M x 67% and 1S:1M x 50% of planting pattern and seed proportion of mung bean, respectively. Intercropping sorghum in a 1:1 planting pattern within 50% seed proportion of mung bean gives 12.54 and 63.65% yield advantages over planting each crop alone. Therefore, 50% (125,000 plants ha-1) mung bean seed proportion with 1S:1M planting pattern are recommended for intercropping in the target area, based on its better compatibility, and yield productivity. Key words: - Seed proportions, planting patterns, Agronomic traits, Yield